A Student Engagement in a Virtual Class by FLIP Learning Application - Amelia Iswandari (STBA LIA - Jakarta, 2022)
Engagement is very crucial in the virtual language learning process and needs to be always maintained. One way to keep learning engagement is the application of the FLIP Learning approach with its four pillars, including Flexible surroundings, Learning Culture. Intentional Content, Professional Educators. This study aimed to find out the occurrence of engagement in virtual Speaking classrooms, as well as pinpoint the most influential pillar of FLIP Learning in the class. The research used a qualitative method by conducting surveys and class observations for data collection. The respondents were 50 students from virtual Speaking classes in semester 1 of the academic year 2021/2022 of STBA LIA Jakarta. It was revealed that learning engagement occurred, and Professional Educators is the most influential factor out of four pillars of FLIP Learning in the virtual Speaking Classes.